Identifying elements of social construction of innovation in knowledge enterprise using memory-work method - Mohammad Saleh Torkestani; Seyed Soroush Ghazinoori; Pedram Jahedi (سیاست نامه علم و فناوری, 2021)
When confronted with new or old challenges, humans are inevitably forced to create new solutions or new formulations of existing solutions. The practice of issue solving in the physical world or the concept of innovation in the mental world have varying connotations across cultures and languages. The present study is an attempt to identify the constituent elements of the social reality of innovation in knowledge-based companies in the context of Persian language in Iran. This study takes an applied, descriptive approach. The research is qualitative in nature and employs the memory-work method in accordance with the social constructivist perspective. The statistical population consists of individuals employed in knowledge-based firms in Guilan Province's Science and Technology Park. Seventy participants were sampled using a non-random sampling procedure. The study showed that the factors of social construction of innovation in knowledge companies fall into two categories. The first consisted of subject-related elements, including patience, exhaustion, curiosity, observing, drive for problem solving, calmness, partiality, fearing, struggling, doubting, and having a personal purpose. The second consisted of object-related elements, including Internet surfing, time passing, changing decor, joking, a noisy setting, a working group, silence, and experimenting. The examination of the elements revealed a conflict between motion and stillness in the subject-related aspects, which has not been observed in past research where stillness in the present time and deferring change to a later time are not present. An analysis of the object-related components revealed that the primary source of innovation was Internet surfing.